Observation of spin flips with a single trapped proton - Ulmer, Stefan; Rodegheri, C. C.; Blaum, Klaus; Kracke, H.; Mooser, A.; Quint, Wolfgang; Walz, J. (Physical review letters, 2011)
Radio-frequency induced spin transitions of one individual proton are observed. The spin quantum jumps are detected via the continuous Stern-Gerlach effect, which is used in an experiment with a single proton stored in a cryogenic Penning trap. This is an important milestone towards a direct high-precision measurement of the magnetic moment of the proton and a new test of the matter-antimatter symmetry in the baryon sector.